UNDERSTANDING DETERMINANTS OF DOMESTIC MERGERS AND ACQUISITIONS THROUGH LITERATURE REVIEW - Kapil, Sheeba; Dhingra, Kanika (Indian Journal of Finance and Banking, 2021)
For a firm entering into M & A is sometimes a choice and other times it is a compulsion. But if a Corporate wants to grow, it has to undergo organic as well as inorganic growth in form of M & A.  The study of determinants of Mergers and Acquisitions has thereby become of utmost importance and relevant in times of intense competition among Firms. The current study explores the determinants of mergers and acquisitions for Domestic deals in India in comparison to other nations. The determinants can be categorized into firm-specific, macro-economic, strategic determinants, financial determinants. Thorough research is done by following a rigorous process from exploring the papers to synthesizing the research. The study also gives insights regarding how the relevance of factors determining mergers and acquisitions is changing in India with an impact of COVID-19 and other global level uncertainties.JEL Classification Codes: F23, F65, G34, L25.